The Xenogamous Nature of Cultural Studies - Burszta, Wojciech J. (Journal of Applied Cultural Studies, 2015)
The aim of the study is to evaluate the xenogamous nature of cultural studies. The author is of the opinion that the word xenogamy that belongs to the biological sciences is worth applying in the form of another metaphor, one relating to the concept of culture as such, culture as an abstract category. The history of this word’s usage, and the resultant connotations and denotations of the concept of culture, show that its meaning is not only constantly evolving, expanding or narrowing, but is in addition constantly being ‘pollinated’ by various areas of social practice. Proving the proposed thesis the author presents the selected works on the concept of culture.